E-Learning: An Evolutionary Study and Strategic Recommendations in Higher Education - Asyifa Eka Maulia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the evolution of e-learning, compare its implementation across various levels of education, and formulate strategic recommendations for optimization at Wiralodra University. Using a qualitative approach through literature review and conceptual analysis, this study traces the development of e-learning from a simple computer-based instruction system (PLATO) to a fully integrated ecosystem through a Learning Management System (LMS). The analysis shows that e-learning in higher education demands a high level of self-regulated learning (SRL) from students, with a focus on developing critical thinking and scientific specialization, distinguishing it from the goal of knowledge transfer at the school level. Although e-learning offers exceptional flexibility and accessibility, its implementation is hampered by the Digital Divide (limited infrastructure and internet access) and the Pedagogical Divide (a tendency toward transference rather than transformation in course design). As a contribution to this understanding, it is recommended that Wiralodra University adopt a proportional blended learning model and provide offline content support to address access issues. Quality optimization must be strengthened through lecturer training focused on online instructional design, as well as the integration of technologies such as Learning Analytics and VR/AR exploration to enhance personalized learning interventions and the quality of practice. This comprehensive strategy is essential to making e-Learning a hub for inclusive and effective innovation.